Effect of Zn addition on the microstructures and mechanical behaviors of As-cast Mg-2.5Y-1Ce-0.5Mn alloy - Xiaoru Zhang; Guixun Sun; Jiaan Liu; Chaojie Che; Mengli Yang; Shuang Han; Daqing Fang; Zhonghao Jiang; Jianshe Lian (Materials Research Express, 2020)
The effect of Zn addition on the microstructures and mechanical behaviors of as-cast Mg-2.5Y-1Ce-0.5Mn alloy was investigated. Microstructure observation demonstrated that with the addition of 1wt%, 3wt% and 5wt% Zn, the ternary phases of LPSO phase, LPSO phase +W-phase and W-phase +T-phase (Mg-Zn-Ce) are precipitated orderly, and the volume fraction of eutectic phases increases. The results of tensile tests demonstrated that with increasing Zn addition, the yield strength $\left({σ }_{YS}\right)$ of as-cast alloys increases continuously while the ultimate tensile strength $\left({σ }_{{\rm{UTS}}}\right)$ and elongation $\left(δ \right)$ increase nonlinearly. Based on the analysis of microstructure, nanoindentation results and deformation surfaces, it found that the ${σ }_{YS}$ is increased by the increased volume fraction of hard ternary phases. The largest $δ $ in 1wt% Zn alloy is contributed from the LPSO phase with an excellent plastic accommodation while the insufficient accommodated role of LPSO phase and the easily broken W-phase deteriorate the ductility of 3wt% Zn alloy. The hard and brittle T-phase also damages the ductility, while the fine grains contribute to the moderate elongation in 5wt% Zn alloy. The ${σ }_{{\rm{UTS}}}$ mainly arises from a sustainable increase of strain hardening ability after yielding that associated with both the high yielding point and excellent ductility.